(untitled) (LEARNing Landscapes, 2015)
The purpose of this action research endeavor was to change the culture of an accuracy view of reading to one of comprehension in a fifth grade classroom. The goal was to establish a common vocabulary and to revalue the process of reading. A constant comparative method of data analysis was used throughout the study to observe changes in students’ view of reading and use of miscue vocabulary. By the end of this study, students actively monitored comprehension, rather than trying to produce an oral reading event with 100% word accuracy.